New taxonomic status of Paralimnellus Emeljanov, 1972 and Dlabolasia Nemesio, 2007 (Hemiptera: Cicadellidae: Deltocephalinae: Paralimnini) - Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2011)
Dlabola (1961) redescribed the species Paralimnus cingulatus Dlabola, 1960 and designated it as type species of a new subgenus, Bubulcus, in Paralimnus Matsumura, 1902. Later, Emeljanov (1972) established the genus Paralimnellus, designating P. cingulatus Dlabola as its type species. Hamilton (1975) and Webb & Heller (1990) treated Bubulcus as a separate genus. According to the Law of Priority of the ICZN (1999), two genus-group names, regardless of their rank within this category (genus or subgenus), cannot have the same type species. Therefore, Bubulcus and Paralimnellus are objective synonyms and the latter, younger, name is invalid. Recently, Nemesio (2007) proposed a new subgeneric name Dlabolasia to replace Bubulcus Dlabola, 1961, because the latter is a junior homonym of Bubulcus Bonaparte, 1854. However, because Paralimnellus, an objective synonym of Bubulcus Dlabola, is an older available name, Paralimnellus must be retained as the replacement name for Bubulcus Dlabola. Thus, according to ICZN Articles 23.3.5 and 60.1, Dlabolasia Nemesio should be treated as a junior objective synonym of Paralimnellus Emeljanov.